Striden mellem pastor Grundtvig og biskop Mynster om bispesuccessionen: Oversættelse af Mynsters latinske landemodetale i 1840 med kommenteret indledning - Rasmussen, Jens; Riising, Anne (Kirkehistoriske Samlinger, 2008)
Through the English legation priest of Nugent Wade (Elsinore) and the Oxford Movement N.F.S. Grundtvig was acquainted with the Church of England’s apostolic succession. It claimed that the Episcopal ministry had been transmitted from the past to the present generation through uninterrupted series of consecration of bishops by placing hands on the new bishop’s head ever since the early Church. From this point of view, already in 1827, Grundtvig claimed that there was a lack of bishops in the Danish State Church. It had no genuine bishops because the line had been interrupted by the Reformation. In Frisprog, 1839, Grundtvig expressed his anger at Bishop J.P. Mynster’s proposal for a new ritual for the consecration of a bishop which talked about transmitting the holy Episcopal ministry. In Grundtvig’s opinion no bishop could pass on rights he did not have personally, this would be false transmission. And since they were not legitimate bishops, they were not to bear the title of bishop; rather, they might be called superintendents. Consequently, J.P. Mynster was the bishop of the Danish State Church, but he did not have the spiritual authority handed over since the ancient apostolic succession. Grundtvig was inspired by the Oxford Movement, albeit without any connection to the Roman Catholic Church. Bishop Mynster replied in his official statement at the diocesan convention of 1840. Warning against the distorted Church of Rome and the fanatical followers who were about to join it, Mynster simply refused to accept the existence of apostolic succession. He thoroughly referred to the New Testament, the Fathers of the early Church, Luther as well as Calvin, and Mynster concluded that the Apostolic Age was without bishops. Therefore, apostolic succession did not exist. Furthermore, it was of no consequence because the clerical ordination constituted a coherent succession of priests in the Danish State Church. Later, Grundtvig fully accepted this point of view in the years after 1855. {Den Christelige Børnelærdom). J. R Mynster maintained that the clerical ordination was the very same for priests, deans and bishops. When the Episcopal ministry was handed over to a new bishop, it meant he was entrusted with the supervision. As regards the title of bishop, only »ridiculous people« (Grundtvig et al) were unaware that the words bishop and superintendent implied the same significance, but the word bishop was well adapted into the Danish language. J.P. Mynster’s official statement in Latin was made at a service of the diocesan convention of 1840, at which also a dean was inducted. It is possible that Grundtvig was present, or he might have heard Mynster’s speech. Probably, he read it in Acta Synodalia Selandiæ. But Grundtvig dissociated from the attitude of the Oxford Movement in 1840-42. Certainly, Mynster’s official statement of 1840 at the diocesan convention must have played a decisive part, however, indirectly.